A Comparative Study of Valuka Sweda and Shatapushpadi Lepa in Janu Sandhi Shula, Shotha and Stabdata w.s.r Amavata - Lakkundi, Shridhar; Gupta, Piyush; Singh, Ratan (International Research Journal of Ayurveda & Yoga, 2023)
Amavata is disorder affecting the population globally with pain, swelling, stiffness of joints. It can be compared with Rheumatoid arthritis based on similar signs and symptoms, with female and male ratio as 3:1. The prevalence of rheumatoid arthritis in most industrialized countries varies between 0.3% and 1%; In India a rough estimate of 0.5 – 0.75% affliction is observed, with two-thirds of patients having mild to-moderate disability and less than 10% having severe disability Within 10 years of disease onset, at least 50% of patients in developed countries are unable to hold down a full-time job. In any form of arthritis involving knee joint not only produces physical disability, but also has crippling effect on psychosocial entity of the individual. So knee joint being an important locomotory and weight bearing joint, deserves special attention in prevention and management strategies for rheumatic diseases. Our Ayurvedic literatures have wealth of resource information regarding the measures preventing the complication and treatment of this disease. Among them are Valuka sweda and shatapushpadi lepa mentioned by Yogaratnakara which are said to have important role to play in reduction of shotha, shula and stabdata in treatment of Amavata. So the knee joint has been specially considered, and effort has been made in this comparative study to evaluate the efficacy of valuka sweda and shatapushpadi lepa in janu sandhi shula, shotha and stabdata w.s r Amavata.